Age-dependent intoxication by larkspur (Delphinium) in Angus steers. (15th September 2018) - Green, B.T.; Gardner, D.R.; Cook, D.; Pfister, J.A.; Welch, K.D.; Keele, J.W.
Abstract: The effect of age on larkspur poisoning of cattle is unknown. An experiment consisting of oral dosing of dried, ground, Delphinium barbeyi to ten Angus steers as yearlings, and again at two years was performed. There was a significant difference between the responses of yearling and two year old steers (P = 0.0015), with yearling steers being more susceptible. These results suggest that the adverse response of Angus cattle to larkspur is age-dependent. Highlights: Larkspurs ( Delphinium spp . ) are a significant problem for cattle grazing on rangelands of the western North America. Oral dosing of dried, ground, Delphinium barbeyi to ten Angus steers as yearlings, and again at two years was performed. There was a significant difference between the responses of yearling and two year old steers (P = 0.0015).